Empirical Study on the Influence of Security Control Management and Social Factors in Deterring Information Security Misbehaviour - Hanifah Abdul Hamid; Dali N.R.S.M. (Institute of Physics Publishing, 2024)
Indexed by SCOPUS/ERA